Anatomies of the Gospels and beyond: essays in honor of R. Alan Culpepper - Parsons, Mikeal Carl; Malbon, Elizabeth Struthers; Anderson, Paul N.; Culpepper, R. Alan (Biblical interpretation series, 2018)
Chapter 6 Mark: John's Photographic NegativeChapter 7 Placing Bethsaida: From Mark to Matthew and Luke to John; Chapter 8 Teaching the Gospel of Mark in Rome; Chapter 9 From Markan Narrative in Print to Markan Narrative in Performance: A Paradigm Shift; Chapter 10 Do You not Yet Trust God's Rule Breaking in on Earth? The Disciples in Mark; Gospel of Luke; Chapter 11 Illuminating "Christ Among the Doctors" (Luke 2:41-52) in the Exegetical Tradition and Select Florentine Renaissance Paintings; Chapter 12 Disability and Dis-ease: Body, Restoration, and Ethics of Reading in Luke's Gospel